The Influence of Transformational Leadership on Construction Services Business Performance Through TQM and Digital Capabilities in the Post-Covid-19 Era - Permana, Erwin; Thalib, Supriadi; Rachbini, Widarto; Wulandjani, Harimurti; Murni, Yetti; Juliana, Juliana (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. The construction industry is one of the many global businesses that have felt the serious impact during the COVID-19 pandemic. Research on the construction services industry in the post-covid-19 era aims to: 1). Analyzing the influence of transformational leadership on company performance. 2) Analyze the influence of transformational leadership on digital capabilities. 3) Analyze the influence of transformational leadership on TQM. 4) Analyzing the influence of digital capabilities on performance, and 5) Analyzing the influence of TQM on performance. This study uses a quantitative approach. The research respondents were 100 leaders of construction service companies in Jakarta, the capital city of Indonesia. Data was collected through a questionnaire instrument. Data analysis was carried out using Structual Equation Model (SEM) With Partial Least Square (PLS). This research was carried out with a series of test scenarios, namely 1). digital capability as a mediator variable without TQM; 2). TQM as a mediator variable without digital capabilities; and 3). Digital capabilities together with TQM become a mediator between transformational leadership and performance. The research results show that without implementing TQM, digital capabilities mediate the relationship between transformational performance. Without digital capabilities, TQM completely mediates the influence of transformational leadership on performance. If digital capabilities and TQM are used as mediation simultaneously, TQM becomes a complete mediating variable in the relationship between transformational leadership and the performance of construction service companies in the post-Covid-19 era. This research opens up opportunities and recommends the emergence of research that integrates TQM-Digital. Keywords: Transformational leadership, digital capabilities, TQM and Performance. Abstrak. Industri konstruksi merupakan salah satu dari sekian banyak bisnis global yang merasakan dampak serius selama pandemi COVID-19. Penelitian pada industry jasa konstruksi dimasa post-covid-19 ini bertujuan untuk: 1). Menganalisis pengaruh kepemimpinan transformasional terhadap kinerja perusahaan. 2) Menganalisis pengaruh kepemimpinan transformasional terhadap kapabilitas digital. 3) Menganalisis pengaruh kepemimpinan transformasional terhadap TQM. 4) Menganalisis pengaruh kapabilitas digital terhadap kinerja, dan 5) Menganalisis pengaruh TQM terhadap kinerja. Penelitian ini menggunakan pendekatan kuantitatif. Responden penelitian adalah 100 orang pimpinan perusahaan jasa konstruksi di Jakarta, ibu kota Indonesia. Data dikumpulkan melalui instrumen kuesioner. Analisis data dilakukan dengan Structual Equation Model (SEM) With Partial Least Square (PLS). Penelitian ini dilakukan dengan serangkaian skenario uji, yakni 1). kapabilitas digital sebagai variabel mediator tanpa TQM; 2). TQM sebagai variabel mediator tanpa Kapabilitas digital; dan 3). Kapabilitas digital secara bersama-sama dengan TQM menjadi mediator antara kepemimpinan transformasional terhadap kinerja. Hasil penelitian menunjukkan bahwa tanpa penerapan TQM, kapabilitas digital memediasi hubungan antara transformasional terhadap kinerja. Tanpa kapabilitas digital, TQM memediasi secara penuh pengaruh antara kepemimpinan transformasional terhadap kinerja. Jika kapabilitas digital dan TQM dijadikan sebagai mediasi secara bersamaan maka TQM menjadi variabel mediasi secara penuh hubungan antara kepemimpinan transformasional leadership terhadap kinerja perusahaan jasa konstruksi dimasa post-Covid-19. Penelitian ini membuka peluang sekaligus merekomendasikan bagi munculnya penelitian yang mengintegrasikan TQM-Digital. Kata Kunci: Kepemimpinan transformasional, kapabilitas digital, TQM dan kinerja.